Assessment of aerobic and anaerobic demands of dinghy sailing at different wind velocities - Vogiatzis, I.; Spurway, N. C.; Wilson, J.; Boreham, C. (The Journal of Sports Medicine and Physical Fitness, 1995)
The aim of this study was to assess the oxygen uptake (VO2), heart rate (HR) and blood lactate concentration ([Lab]) during actual dinghy sailing at different wind velocities. Eight top class Laser sailors volunteered to participate in the study. In the laboratory, each subject performed an incremental exercise test on a cycle ergometer to the point of exhaustion. Maximum oxygen uptake (VO2max) and maximum heart rate (HR max) were assessed by means of a Cosmed K2 (K2) portable oxygen analyser while the accuracy of the K2 was simultaneously examined by comparing it with the Douglas bag method. On water each subject underwent a 10 minute continuous upwind sailing test. The average percentages of VO2max and HR max during sailing and the post-test [La(b)] were 39 +/- 6%, 74 +/- 11% and 2.3 +/- 0.8 mM, respectively. Values of the three measured variables for each subject were significantly correlated to wind velocity (r = 0.73, 0.87 and 0.88, respectively). The results of the study suggest that the metabolic and cardiorespiratory demands of dinghy sailing predominantly depend on the wind conditions. Aerobic capacity is only moderately taxed in dinghy sailing and should not be emphasized in training, whereas anaerobic metabolism plays an increasing role in stronger winds.